Propuesta Metodológica Para La Planificación Del Diseño Arquitectónico De Viviendas De Interés Social Sustentables Y Flexibles - Suárez Brito, Marco Vinicio (2017)
This research studies a methodological proposal for the planning of the architectural design of sustainable and flexible social housing, arises from the need to find guidelines and parameters necessary to allow the proper functioning of social housing, covering the needs and expectations of users And that allows them to carry out their daily activities in adequate conditions of comfort, always seeking that this housing unit manage to integrate to its natural environment and built maintaining a suitable urban image and environmentally healthy, that the concept of social housing is not only relegated to the appearance Economic, if not managing concepts of quality sustainability and flexibility that allows users to obtain basic decent housing and that over time is able to adapt to the new needs of the family, through extensions and improvements that allows it to be completed Sec n the economic possibilities of the family. The objective of the research was to develop a methodological proposal through a review of cases referring to local and world level, for it was used a qualitative methodology with a bibliographical approach through the theoretical revision of scientific journals to establish the conceptualization of the variables related to The subject under study, and which were a basis for finding an adequate methodology for planning the architectural design of sustainable and flexible social housing. This methodology aims to be a tool that seeks to improve every day the architectural design of social housing in the most needy population sectors, for this reason the present research aims to help find efficient solutions to the great housing problem Of social interest in cities in constant growth.